Peran dan Strategi JTV Surabaya dalam Menghadapi Konvergensi Media - Berie Poetra Akbar; Hikmah Lailatul Fitriyah; Lizza Arnofia Choirunnisa; Rafly Yuvindra Maulidan; Irwansyah Irwansyah (Syntax Corporation Indonesia, 2024)
The purpose of this research is to find new empirical things related to convergence 3.0 at JTV which is. Case studies were used as a research method. In this study, a case study was conducted at JTV to find out the role and strategy of JTV Surabaya in facing media convergence. This study collected data through observation and literature study. Data collection techniques were carried out by observation, interviews, and literature studies. Observations were made through the JTV https://www.portaljtv.com/ website and visited the JTV office or PT Pojok Pitu Media with the address at Jl A Yani 88 Surabaya, East Java. Interviews were also conducted with the Editor-in-Chief and HRD of JTV at the office. Furthermore, literature study is the process of finding literature that supports research. Journals and other documents related to this study are secondary data in this study. As a result, for the convergence to be successful, of course, the hard work of all editors is needed. Including journalists in it so that they can manage the content needed by the audience or viewers in each platform. Be it television, social media or news portals. In addition, they are also required to be credible, fast and accurate in accordance with the rules of journalistic ethics or KEJ in presenting content to many platforms or see the convergence of newsroom 3.0.